College Experiences and Outcomes Among International Undergraduate Students at Research Universities in the United States: A Comparison to Their Domestic Peers - Kim, Young K.; Collins, Christopher S.; Rennick, Liz A.; Edens, David (Journal of International Students, 2017)
Using a large dataset from a state education system, this study examined the experience of international college students in the United States as well as the connection to their cognitive, affective, and civic outcomes. The study utilized data from the 2010 University of California Undergraduate Experience Survey (UCUES) and a sample of 35,146 junior and senior undergraduate students across 10 campuses. The results of this study showed that international students may uniquely experience college and may not benefit from those experiences as much as their domestic peers. Furthermore, this study identified a broad range of college experiences that contribute to the key outcomes for international students. The study discusses the theoretical and practical implications of the findings